Season and Flow Drive Productivity of a Regulated River - Darren P. Giling; Ben Broadhurst; Fiona Dyer; Michael Grace; Klaus Joehnk; Paul J. McInerney; Carmel Pollino; Gavin Rees; Ashmita Sengupta; Alica Tschierschke; Ross M. Thompson (Ecosystems, 2025)
Flow regimes of river ecosystems worldwide have undergone substantial changes because of water resource development, altering the way in which organic matter is generated and cycled throughout entire river catchments. Flow–ecology studies have focused on structural variables measured at small spatial scales. This creates a challenging mismatch when applying adaptive flow management for ecosystem functioning at a catchment or regional scale. Here, we sought to inform flow management by evaluating the drivers of ecosystem metabolism in a regulated river and assessing our ability to predict metabolism at unmonitored locations. We estimated rates of ecosystem metabolism from high-frequency monitoring of dissolved oxygen concentration at eight sites on the Lachlan River of Australia’s Murray–Darling Basin. We then applied a spatio-temporal stream network model to predict metabolism at unmonitored locations using only remotely sensed and gauging station predictor variables. Gross primary productivity (GPP) was higher at sites with lower mean annual discharge, and strong seasonal patterns in rates of productivity tended to be disrupted by rising flows. Similarly, ecosystem respiration (ER) was higher at sites with lower mean annual discharge and lower annual flow variation, but increased slightly in response to higher daily flows. Predictions at validation sites were generally accurate, albeit with substantial site-to-site variation. Our results suggest that flow changes may have altered metabolic rates from conditions prior to water abstraction and dam construction. These findings will assist in managing flows for ecosystem function outcomes and support extrapolation from monitored sites to the broad scales required for evaluating catchment-scale outcomes of river management.

Measuring the Response Diversity of Ecological Communities Experiencing Multifarious Environmental Change - Francesco Polazzo; Romana Limberger; Frank Pennekamp; Samuel R. P.‐J. Ross; Gavin L. Simpson; Owen L. Petchey (Global Change Biology, 2024)
The diversity in organismal responses to environmental changes (i.e., response diversity) plays a crucial role in shaping community and ecosystem stability. However, existing measures of response diversity only consider a single environmental variable, whereas natural communities are commonly exposed to changes in multiple environmental variables simultaneously. Thus far, no approach exists to integrate multifarious environmental change and the measurement of response diversity. Here, we show how to consider and quantify response diversity in the context of multifarious environmental change, and in doing so introduce a distinction between response diversity to a defined or anticipated environmental change, and the response capacity to any possible set of (defined or undefined) future environmental changes. First, we describe and illustrate the concepts with empirical data. We reveal the role of the trajectory of environmental change in shaping response diversity when multiple environmental variables fluctuate over time. We show that, when the trajectory of the environmental change is undefined (i.e., there is no information or a priori expectation about how an environmental condition will change in future), we can quantify the response capacity of a community to any possible environmental change scenario. That is, we can estimate the capacity of a system to respond under a range of realistic or extreme environmental changes, with utility for predicting future responses to even multifarious environmental change. Finally, we investigate determinants of response diversity within a multifarious environmental change context. We identify factors such as the diversity of species responses to each environmental variable, the relative influence of different environmental variables and temporal means of environmental variable values as important determinants of response diversity. In doing so, we take an important step towards measuring and understanding the insurance capacity of ecological communities exposed to multifarious environmental change.

An investigation into the stability and degradation of plastics in aquatic environments using a large-scale field-deployment study - Beatrix Theobald; Regis Risani; Lloyd Donaldson; James H. Bridson; Joanne M. Kingsbury; Olga Pantos; Louise Weaver; Gavin Lear; Xavier Pochon; Anastasija Zaiko; Dawn A. Smith; Ross Anderson; et al. (Science of The Total Environment, 2024)

Exercise-induced skeletal muscle angiogenesis: impact of age, sex, angiocrines and cellular mediators - Mark Ross; Christopher K. Kargl; Richard Ferguson; Timothy P. Gavin; Ylva Hellsten (European Journal of Applied Physiology, 2023)
Exercise-induced skeletal muscle angiogenesis is a well-known physiological adaptation that occurs in humans in response to exercise training and can lead to endurance performance benefits, as well as improvements in cardiovascular and skeletal tissue health. An increase in capillary density in skeletal muscle improves diffusive oxygen exchange and waste extraction, and thus greater fatigue resistance, which has application to athletes but also to the general population. Exercise-induced angiogenesis can significantly contribute to improvements in cardiovascular and metabolic health, such as the increase in muscle glucose uptake, important for the prevention of diabetes. Recently, our understanding of the mechanisms by which angiogenesis occurs with exercise has grown substantially. This review will detail the biochemical, cellular and biomechanical signals for exercise-induced skeletal muscle angiogenesis, including recent work on extracellular vesicles and circulating angiogenic cells. In addition, the influence of age, sex, exercise intensity/duration, as well as recent observations with the use of blood flow restricted exercise, will also be discussed in detail. This review will provide academics and practitioners with mechanistic and applied evidence for optimising training interventions to promote physical performance through manipulating capillarisation in skeletal muscle.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Genetic diversity within and among landraces of pearl millet (Pennisetum glaucum) under farmer management in West Africa - Carlos S. Busso; Katrien M. Devos; Gavin Ross; Michael Mortimore; William M. Adams; Michael J. Ambrose; Sharon Alldrick; Michael D. Gale (Genetic Resources and Crop Evolution, 2000)

Polygalacturonase gene expression in kiwifruit: relationship to fruit softening and ethylene production - Zhong-Yan Wang; Elspeth A. MacRae; Michele A. Wright; Karen M. Bolitho; Gavin S. Ross; Ross G. Atkinson (Plant Molecular Biology, 2000)

Gene encoding polygalacturonase inhibitor in apple fruit is developmentally regulated and activated by wounding and fungal infection - Chenglin Yao; William S. Conway; Ruihua Ren; David Smith; Gavin S. Ross; Carl E. Sams (Plant Molecular Biology, 1999)

Apple ACC-oxidase and polygalacturonase: ripening-specific gene expression and promoter analysis in transgenic tomato - Ross G. Atkinson; Karen M. Bolitho; Michele A. Wright; Teresa Iturriagagoitia-Bueno; Suzanne J. Reid; Gavin S. Ross (Plant Molecular Biology, 1998)